2021
DOI: 10.3390/ijms22052504
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Manifestations of Epithelial–Mesenchymal Plasticity of Circulating Tumor Cells in Breast Cancer Patients

Abstract: To date, there is indisputable evidence of significant CTC heterogeneity in carcinomas, in particular breast cancer. The heterogeneity of CTCs is manifested in the key characteristics of tumor cells related to metastatic progression – stemness and epithelial–mesenchymal (EMT) plasticity. It is still not clear what markers can characterize the phenomenon of EMT plasticity in the range from epithelial to mesenchymal phenotypes. In this article we examine the manifestations of EMT plasticity in the CTCs in breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The CellSearch ® system technology (Menarini-Silicon Biosystems) Immunomagnetic cell selection system Antibody-labeled magnetic nanoparticles that target epithelial cell adhesion molecules of CTCs [29] AdnaTest Tumor cell enrichment based on magnetic beads that are coupled to a mixture of antibodies [30] MagSweeper…”
Section: Technology Detection Methods Description Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CellSearch ® system technology (Menarini-Silicon Biosystems) Immunomagnetic cell selection system Antibody-labeled magnetic nanoparticles that target epithelial cell adhesion molecules of CTCs [29] AdnaTest Tumor cell enrichment based on magnetic beads that are coupled to a mixture of antibodies [30] MagSweeper…”
Section: Technology Detection Methods Description Referencesmentioning
confidence: 99%
“…The isolation and capture of CTCs based on biological characteristics of those heterogeneous cells utilize different biological markers expressed in the cells ( Table 2 ) [ 18 , 19 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The first data describing the detection and characterization of carcinoma cells in the systemic circulation (bone marrow) based on cytokeratin and MUC-1 glycoprotein expression in epithelial cancer cells, but not in healthy cells, were published 25 years ago [ 63 ].…”
Section: Ctc Isolation and Detection Techniquesmentioning
confidence: 99%
“…To generate the transgenic construct pTol2-Cca.actb-GCaMP6s ( Figure 1 A), Tol2-elavl3-GCaMP6s obtained from Addgene (#59531, Watertown, MA, USA) and pT2/carp_actin_P-Abcc4-Flag-carp_actin_pA constructed in our previous study [ 61 ] were double digested using Hin d III and Eco R I from Fermentas (Burlington, NJ, Canada). The desired DNA fragments were recovered through electrophoresis and subsequent gel purification using a kit from Bioer (Hangzhou, China).…”
Section: Methodsmentioning
confidence: 99%
“…1a). CD45 ─ CECs were identified based on the expression of one or more epithelial markers: KRT 5,7,8,17,18,19, EpCAM, and CDH1 (E-cadherin) (Fig. 1b).…”
Section: Detection Of Cecsmentioning
confidence: 99%
“…CTCs are highly heterogeneous, and only a few of them can survive and form metastases 5 . Many studies showed that breast CTCs possess specific stem and epithelialmesenchymal transition (EMT) properties [6][7][8][9][10] , while the molecular repertoire of CTCs varies from patient to patient 6 . Deciphering CTC heterogeneity is thought to be a vital issue for identifying metastasis-initiating cells and therapeutic targets for the prevention of metastasis.…”
Section: Introductionmentioning
confidence: 99%